(untitled) (Research, Society and Development, 2020)
The acerola agro-industrial waste is rich in fibers and substances that have antioxidant potential. Therefore the objective of this study was to elaborate, characterize microbiologically and sensorially, a cookie from the acerola agro-industrial waste. The cookies are analyzed microbiologically (total bolores quantification; total coliforms and coliforms at 45 ° C) and sensoryly, studying acceptance in relation to the attributes of texture, flavor, color and swetness, as well as purchase intention. A cookie formulation, using the acerola agroindustrial residue does not presented microbiological contamination, being according the current legislation and all the sensory attributes present good medium acceptance or that affect, positively, the medium obtained for the purchase intention. In this way, was verified that the elaboration of the cookie, from the acerola agro-industrial waste shows a viable option for the bread industry, with great potential in nutritional, functional, microbiological stability and sensory acceptance , can to be introduced into the food of the population, as a way of taking advantage of the waste.